2020
DOI: 10.1177/1071100720910422
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Medicine for the Orthopedic Foot and Ankle Surgeon

Abstract: Nuclear medicine has been widely applied as a diagnostic tool for orthopedic foot and ankle pathology. Although its indications have diminished with improvements in and the availability of magnetic resonance imaging, nuclear medicine still has a significant and valuable role. The present article offers a comprehensive and current review of the most common nuclear imaging modalities for the orthopedic foot and ankle surgeon. Methods discussed include bone scintigraphy, gallium citrate scintigraphy, labeled-leuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 83 publications
(174 reference statements)
0
10
0
Order By: Relevance
“…Up to 98% of patients may demonstrate osteolysis on radiographs, and this finding may even be expected due to stress shielding with some implants. 27,84 Furthermore, osteolysis often occurs within the cancellous bone of the distal tibia and proximal talus, and because of the thick cortical bone surrounding this area, a large degree of calcium can be lost before it becomes apparent on plain radiographs. Additionally, the metallic components of the implant can obscure visualization of osteolysis at the bone-implant interface.…”
Section: Clinical Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to 98% of patients may demonstrate osteolysis on radiographs, and this finding may even be expected due to stress shielding with some implants. 27,84 Furthermore, osteolysis often occurs within the cancellous bone of the distal tibia and proximal talus, and because of the thick cortical bone surrounding this area, a large degree of calcium can be lost before it becomes apparent on plain radiographs. Additionally, the metallic components of the implant can obscure visualization of osteolysis at the bone-implant interface.…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…These imaging modalities can identify areas of increased physiologic activity in the bone surrounding the prosthesis that can indicate suspicion for implant loosening. 84 Bone scintigraphy has been shown to be highly nonspecific in the hip arthroplasty literature, with variable false-positive and false-negative rates of detecting periprosthetic osteolysis and loosening (Figure 2). 18 Initial studies, however, have found SPECT/CT to be useful in evaluating suspected loosening of TAA prostheses, and to differentiate aseptic loosening from other sources of pain following TAA.…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…51 Up to 98% of patients may show some degree of osteolysis on postoperative radiographs. 23,94 Even in asymptomatic patients, periodic radiographic surveillance should be performed postoperatively so that any clinically silent cystic lesions can be detected early. It is crucial to monitor cysts radiographically for progression, as large, progressive cysts can increase the risk of fracture and the need for revision surgery.…”
Section: Is It Fractured?mentioning
confidence: 99%
“…68 SPECT may also be used and can identify areas of increased physiologic activity at the bone-implant interface, which may represent loosening or cyst formation. 39,70,94 Metal artifact reduction MRI is also useful and can identify significantly more osteolysis and edema in painful TAR compared to traditional MRI techniques. 17 Multiple factors have been identified as potential etiologies for the development of cysts and osteolysis.…”
Section: Is It Fractured?mentioning
confidence: 99%
“…The previous use of three-phase bone scintigraphy in diabetes patients with neuropathy suggested increased blood flow to bone but the planar imaging has low anatomical resolution [9]. However, the introduction of hybrid Single Photon Emission Computed Tomography/ Computed Tomography (SPECT/CT) in nuclear medicine has improved the diagnostic potential of bone scintigraphy [10]. Combining SPECT and CT considerably increases bone scan image quality (attenuation correction), anatomic localization and diagnostic accuracy [11].…”
Section: Introductionmentioning
confidence: 99%